Konsep dan Fungsi Algoritma Pemrograman - Hani Rarti Syahara Harahap; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2023)
An introduction to algorithms begins with a basic understanding of the algorithm itself. An algorithm is an organized sequence of steps to solve a problem, taking into account systematic sequence and logical goals. Meanwhile, a programming algorithm is a set of instructions that a computer is asked to execute to solve a problem. Good mastery of programming algorithms is absolutely necessary for people who want to study computer science or mathematics. Therefore, this article aims to help readers who want to learn the importance of programming algorithms through basic concepts. This paper uses a literature review method from various types of existing sources to discuss history, function and properties, algorithm structure, notationincluding natural, pseudocode and flowcharts.